Surgical treatment of gastrointestinal stromal tumour of the rectum in the era of imatinib. Issue 8 (13th May 2015) - Wilkinson, M J; Fitzgerald, J E F; Strauss, D C; Hayes, A J; Thomas, J M; Messiou, C; Fisher, C; Benson, C; Tekkis, P P; Judson, I
Abstract: Background: Gastrointestinal stromal tumours (GISTs) of the rectum often require radical surgery to achieve complete resection. This study investigated the management and outcome of surgery for rectal GISTs and the role of imatinib. Methods: A cohort study was undertaken of patients identified from a database at one tertiary sarcoma referral centre over a continuous period, from January 2001 to January 2013. Results: Over 12 years, 19 patients presented with a primary rectal GIST. Median age was 57 (range 30–77) years. Neoadjuvant imatinib was used in 15 patients, significantly reducing mean tumour size from 7·6 (95 per cent c.i. 6·1 to 9·0) to 4·1 (2·8 to 5·3) cm ( P < 0·001). Nine of these patients underwent surgical resection. Imatinib therapy enabled sphincter-preserving surgery to be undertaken in seven patients who would otherwise have required abdominoperineal resection or pelvic exenteration for tumour clearance. Neoadjuvant imatinib treatment also led to a significant reduction in mean(s.d.) tumour mitotic count from 16(16) to 4(9) per 50 high-power fields ( P = 0·015). Imatinib was used only as adjuvant treatment in two patients. There were three deaths, all from unrelated causes. Eleven of the 13 patients who underwent resection were alive without evidence of recurrence at latest follow-up, with a median disease-free survival of 38 (range 20–129) months and overall survival of 62 (39–162) months. Conclusion: The use of neoadjuvant imatinib for rectal GISTs significantly decreased both tumour size and mitotic activity, which permitted less radical sphincter-preserving surgery. Abstract : Neoadjuvant imatinib therapy was useful